Quedan los huesos - Ward, Jesmyn (Nuevos tiempos (Madrid, Spain), 2013)
Enduring a hardscrabble existence as the children of alcoholic and absent parents, four siblings from a coastal Mississippi town prepare their meager stores for the arrival of Hurricane Katrina while struggling with such challenges as a teen pregnancy and a dying litter of prize pups.